From Ancient Mausoleums to Rotunda Buildings of the Classicist Period. The Genesis of Form and Construction - Klimenko, Julia G. (Actual Problems of Theory and History of Art, 2015)
The author of the article examines the examples of using annular barrel vault with central pier in the Late Antique domed constructions. Studies of such buildings in the 16th–18th centuries did a lot for the emergence of the similar constructions in the architecture of that period. Architects of Western Europe adopted Ancient Roman engineering experience, which allowed them to use rotunda forms not only in the church architecture or fortification, but in residential constructions as well. Its wide expansion into palatial residences, villas, and particular private hotels built in the age of Classicism has contributed to significant changes in the outward appearance of buildings. Descriptions of annular barrel vault with central pier are left in treatises, ouvrages and practical manuals published within that period. The knowledge of these, together with architectural analysis of the surviving buildings, whose representational domed lounges are based on the said type of vault, help identify characteristic features of numerous edifices created by representatives of various West European architectural schools. Research of the use of such constructions in Russian architecture both via surviving historical monuments and the drafts of lost buildings or unrealized designs is under consideration in the article. This study is useful for architectural attribution of the monuments of Russian Classicism.